Evaluation of dentin topography after Er, Cr: YSGG laser irradiation and phosphoric acid etching using AFM, SEM and contact angle - Saja Qasim Salman; Basima Mohammed Ali Hussein (Iraqi Journal of Laser, 2026)
Received 7 Jan. 2024; Revised 7 Mar. 2024; Accepted 17 Mar.2024; Published online 15 Jun. 2024 Corresponding Author: saja.qasem2102m@ilps.uobaghdad.edu.iq